Financial amplification mechanisms and the Federal Reserve's supply of liquidity during the crisis - Asani Sarkar; Jeffrey Shrader (Federal Reserve Bank of New York, 2010)
The small decline in the value of mortgage-related assets relative to the large total losses associated with the financial crisis suggests the presence of financial amplification mechanisms, which allow relatively small shocks to propagate through the financial system. We review the literature on financial amplification mechanisms and discuss the Federal Reserve's interventions during different stages of the crisis in terms of this literature. We interpret the Fed's early-stage liquidity programs as working to dampen balance sheet amplifications arising from the positive feedback between financial and asset prices. By comparison, the Fed's later-stage crisis programs take into account adverse-selection amplifications that operate via increases in credit risk and the externality imposed by risky borrowers on safe ones. Finally, we provide new empirical evidence that increases in the amount outstanding of funds supplied by the Fed reduce the Libor-OIS spread during periods of high liquidity risk. In contrast, reductions in the Fed's liquidity supply in 2009 did not increase the spread. Our analysis has implications for the impact on asset prices of a potential withdrawal of liquidity supply by the Fed.
Keywords: G01; G18; G21; G32; 330; Financial amplification mechanism; Federal Reserve liquidity facilities; credit risk; liquidity risk; Libor-OIS spread; Geldpolitik; Gesamtwirtschaftliche Liquidität; Finanzmarkt; Verlust; Zentralbank; Bankbilanz; USA